PREDISPOSING FACTORS FOR THE INCIDENCE OF SUICIDE IN YOUNG PEOPLE - Cristina Alves da Silva Lima, Hellen; Denilson Aurélio Soares, Cicero; Lívia Silva Fonseca Moreira de Medeiros, Renata; Silva Oliveira, Geane; Barros de Quental, Ocilma (Health and Society, 2023)
Introduction: Suicide stands out as a global public health problem, as this practice intentionally involves the act of causing one’s own death. Thus, several factors and circumstances contribute to such an event occurring. In view of the above, this study is justified by its academic, scientific and social relevance, whose purpose is to put on the agenda all epidemiological aspects and risk factors that are directly related to the incidence of care among young people. In this respect, the relevance of this research aims at contributing to science and notoriety in the face of this social problem in which suicide encompasses. Objective: To evaluate the main factors that trigger the risk of suicide in the young population. Methodology: The methodology selected for the basis of this study was the integrative literature review, with a descriptive approach. This integrative review will be carried out through data searches through the scientific bases: LILACS, SCIELO and BDENF. Results and Discussion: Consequently, the main risk factors for suicide among adolescents are the presence of stressful life events, exposure to different types of violence, drug use, family history of suicide, family problems, financial problems, and they are shown to be related to media influence. In addition, the literature points out that the male public is more likely to commit suicide. Conclusion: Considering that this research highlights and emphasizes the importance of knowing the predisposing factors for the incidence of suicide, it is important to take into account the need to develop strategies and prevention to reduce risks. In this sense, it is proposed to strengthen support networks for young people.